Femoral Neck Stress Fractures and Imaging Features of Femoroacetabular Impingement. Issue 6 (13th January 2015) - Goldin, Michael; Anderson, Christian N.; Fredericson, Michael; Safran, Marc R.; Stevens, Kathryn J.
Abstract: Background: Prior literature has suggested an association between the radiographic signs of femoroacetabular impingement (FAI) and femoral neck stress fractures (FNSF) or femoral neck stress reactions (FNSR). At the time of the writing of this article, no study has described the association of FAI and FNSF/FNSR along with the need for surgical intervention and outcomes. Objective: To determine the prevalence of radiographic features of FAI in patients diagnosed with FNSF. Design: Retrospective case series. Setting: Tertiary care, institutional setting. Patients: A medical records search program (Stanford Translational Research Integrated Database Environment, Stanford University, California) was used to retrospectively search for patients 18‐40 years old with a history of FNSF or FNSR. The records were obtained from the period July 25, 2003, to September 23, 2011. Methods: For assessment of risk factors, plain radiographs and magnetic resonance imaging studies were reviewed for features of cam or pincer FAI. Medical records were reviewed to determine whether patients required operative intervention. Main Outcome Measures: Incidence of abnormal alpha (α) angle, abnormal anterior offset ratio, abnormal femoral head‐neck junction, coxa profunda, positive crossover sign, and abnormal lateral center‐to‐edge angle. Results: Twenty‐one female and 3 male participants (mean age 27 years, range 19‐39 years) were identified with magnetic resonance imaging evidence of femoral neck stress injury. Cam morphology was seen in 10 patients (42%). Pincer morphology could be assessed in 18 patients, with coxa profunda in 14 (78%) and acetabular retroversion in 6 (14%). Features of combined pincer and cam impingement were observed in 4 patients (17%). Seven patients (29%) had operative intervention, with 3 (12%) requiring internal fixation of their femoral neck fractures, and all had radiographic evidence of fracture union after surgery. Four patients (17%) had persistent symptoms after healing of their FNSF with conservative treatment and eventually required surgery for FAI, 3 had no pain at final follow‐up 1 year post‐surgery, and one patient was lost to follow‐up. Conclusion: The results of the current study suggest that patients in the general population with femoral neck stress injuries have a higher incidence of bony abnormalities associated with pincer impingement, including coxa profunda and acetabular retroversion, although it is unclear whether pincer FAI is a true risk factor in the development of FNSF.